G.P.142: A new EMD gene missense mutation in exon 1 leads to absence of emerin and is responsible for X-linked dilated cardiomyopathy with conduction defects and arrhythmias and almost elusive skeletal muscle features - Ben Yaou, R.; Gerard, M.; Chami, K.; Sehier, A.; Belin, A.; Labombarda, F.; Richard, P.; Bonne, G.; Leturcq, F.; Chapon, F. (Neuromuscular disorders : NMD, 2014)
Mutations in the EMD gene, encoding emerin, lead to X-linked Emery-Dreifuss muscular dystrophy (EDMD). Although always associated with EDMD, an almost exclusive cardiac involvement was found in exceptional patients carrying EMD gene mutations. We here report 2 brothers belonging to a family where 9 affected male subjects developed dilated cardiomyopathy (DCM) with conduction defects and arrhythmias. The oldest brother of 53years developed DCM since 49years and requiring implantable cardioverter defibrillator (ICD) implantation. He subsequently developed atrio-ventricular and ventricular conduction defects as well as ventricular arrhythmias at 52years that required ICD upgrading and additional pacemaker implantation. His youngest brother aged 45years was also affected. The family history showed several affected members: a third brother who died after cardiac transplantation at 38years, a fourth brother who died suddenly at 50years, two maternal uncles and cousins died in their 5th or 6th decades among them 2 were diagnosed as arrhythmogenic right ventricular dysplasia. An X-linked mode of inheritance was therefore suspected and DMD gene analysis did not show any exonic deletion or duplication or exon 1 point mutation. Further neurological assessment of the oldest brother showed neither muscle weakness nor joint contractures whereas hands and legs were slightly hypotrophic. CPK were at normal level and needle electromyography examination showed normal pattern. Deltoid muscle biopsy was normal as were protein immunohistochemical studies including dystrophin, desmin, myotilin and caveolin 3 while emerin staining was totally absent. Subsequent EMD gene analysis revealed a new missense mutation in exon 1 (c.65C>T, p.Pro22Leu). In addition to the 2 previously reported families with a close emerin mutation (p.delK37) and an exclusive cardiac disease, our family further indicates that emerin protein is crucial for correct cardiac function.